Evaluation of synchronization protocols for artificial insemination with and without estrogens in heifers - Guillen-Alvarado, María Carolina (2025)
Reproduction is basic for any livestock production system, and reproductive biotechnologies help in farm management. The use of two synchronization protocols for timed artificial insemination (TAI) with (P4E2) and without (GnRH-PG) estradiol in heifers (30 Brahman and 30 Simbrah F1) was evaluated. Ultrasonography was performed on the protocol's application days and 7 days post-TAI to evaluate the ovarian response. Blood samples were collected from 24 heifers in the experiment to assess progesterone concentrations during and after the synchronization protocol for TAI. Pregnancy outcomes were determined on day 35 post-breeding. Additionally, a field trial was conducted using the same experimental protocols, focusing solely on pregnancy assessment. Regarding the response in ovarian activity, animals treated with P4E2 presented a greater number of class 3 follicles on days 7 and 9 than those treated with GnRH-PG (p = 0.0413). While, on the same days, in the total number of class 1 follicles (TF1), animals synchronized with P4E2 presented less quantity than those synchronized with GnRH-PG (p = 0.0295). Regarding progesterone levels, there was no difference between treatments (p = 0.3483). For pregnancy diagnosis 1 (DP1), only animals belonging to the Simbrah F1 breed group got pregnant, and the cumulative pregnancy diagnosis (DPA) was affected by the breed group (p = 0.0169), not by the protocols. In both the experiment and the field trial, it was shown that the protocols had a similar performance in the evaluations carried out and in the percentage of pregnancy obtained in each protocol, which indicates that both protocols are viable for the synchronization of beef heifers for timed artificial insemination.